“Padi Lingko” to Reduce Hexavalent Chromium Levels (Cr(VI)) in Citarum River Water Sample - Aeni, Suci Rizki Nurul; Nurdin, Nurdin; Ansori, Ikhsan Faisal (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Clean water is increasingly difficult to obtain, even though water is a chemical compound that is very important for living creatures' lives. Industrial and domestic community waste are a big problem in polluting the Citarum River, causing the water to become unfit. One of the toxic heavy metals found in Citarum River water is chromium (Cr(VI)). The technique that can be used to remove the heavy metal Cr(VI) in Citarum river water samples is adsorption using biological material (biosorption). Biosorption is the process of absorbing metal ions by materials originating from nature. In this research, jengkol peel was used. A modification of this research from previous research is the design of the